2021
DOI: 10.1021/jacs.1c03992
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study in Catalyst Generality: Simultaneous, Highly-Enantioselective Brønsted- and Lewis-Acid Mechanisms in Hydrogen-Bond-Donor Catalyzed Oxetane Openings

Abstract: Generality in asymmetric catalysis can be manifested in dramatic and valuable ways, such as high enantioselectivity across a wide assortment of substrates in a given reaction (broad substrate scope) or as applicability of a given chiral framework across a variety of mechanistically distinct reactions (privileged catalysts). Reactions and catalysts that display such generality hold special utility, because they can be applied broadly and sometimes even predictably in new applications. Despite the great value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 95 publications
2
44
0
Order By: Relevance
“…Along this line, the Jacobsen group reported enantioselective addition of TMSBr to oxetanes giving silylated bromohydrins. 7,25 This work and the control experiment with TMSOTf corroborate our assumption that silylated bromohydrin 5b is an intermediate in this reaction.…”
Section: Scheme 2 Co-catalyzed Functionalization Of Oxetanes Involving Ring-openingsupporting
confidence: 81%
“…Along this line, the Jacobsen group reported enantioselective addition of TMSBr to oxetanes giving silylated bromohydrins. 7,25 This work and the control experiment with TMSOTf corroborate our assumption that silylated bromohydrin 5b is an intermediate in this reaction.…”
Section: Scheme 2 Co-catalyzed Functionalization Of Oxetanes Involving Ring-openingsupporting
confidence: 81%
“… 45 Notable studies have been reported by Jacobsen and co-workers who reported the thiourea-catalyzed asymmetric ring-opening of aziridines with hydrogen chloride, 46 and more recently the desymmetrization of oxetanes with TMSBr and a chiral squaramide as catalyst. 47 , 48 …”
Section: Fluorination Via Solid–liquid Phase-transfer: Hydrogen Bondi...mentioning
confidence: 99%
“…72 By using silyl bromide 163 , an enantioselective ring opening of oxetanes 162 upon nucleophilic addition of the bromide was achieved, leading to 1,3-halohydrins 164 , which can serve as valuable precursors for further derivatizations. However, in a mechanistic study, 73 the authors showed that competing Lewis acid and Brønsted acid pathways were possible in this reaction leading to the same product.…”
Section: Bifunctional and Cooperative Co-catalysis Strategiesmentioning
confidence: 99%